Handbook of research on computerized occlusal analysis technology applications in dental medicine - Kerstein, Robert B.; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book explores the use of digital tools in dentistry, including their evolution, as well as evidence-based research on the benefits of technological tools versus non-digital occlusal indicators"--Provided by publisher.
History of the T-scan system development from 1984 to the present day / Robert B. Kerstein, DMD -- The limitations of traditional non-digital occlusal indicators when compared to the T-Scan computerized occlusal analysis technology / Sarah Qadeer, BDS, MSD -- Precision and reliability of the T-Scan III system: analyzing occlusion and the resultant timing and distribution of forces in the dental arch / Bernd Koos -- T-Scan 8 recording dynamics, system features, and clinician user skills / Robert B. Kerstein, DMD, Robert Anselmi -- Adding technology to diagnostic methods / John C. Radke, BM, MBA -- Joint vibration analysis (JVA) / Ray M. Becker, DDS, FAGD -- Employing T-Scan synchronized with electromyography to treat chronic occluso-muscle disorder / Robert B. Kerstein, DMD -- Occlusal considerations in the hypersensitive dentition / Nick Yiannios, DDS -- Detecting and quantifying cervical dentin hypersensitivity using air indexing combined with the T-Scan system / Thomas A. Coleman, DDS -- The management of advanced tooth wear using the T-Scan/BioEMG synchronization module / Teresa Sierpinska -- Orthodontic T-Scan applications / Julia Cohen-Levy, DDS, MS, PhD -- Digitalized implant occlusion with the T-Scan system / Jinhwan Kim, DDS, MS, PhD -- Computerized occlusal analysis in occlusal splint therapy / Roger Solow, DDS -- Centric relation records and T-Scan occlusal analysis of centric relation prematurities / Roger Solow, DDS -- T-Scan as a patient education tool / John R. Droter, DDS -- T-Scan case finishing applications in aesthetic dentistry assisted by the iTero digital impression system: a case report / Christopher J. Stevens, DDS -- Transcutaneous electrical nerve stimulation (TENS) combined with the T-Scan system: a case report / Curtis Westersund, DDS -- Periodontal treatment and computerized occlusal analysis / Nicolas Cohen, DDS, MS, PhD -- Digital occlusal force distribution patterns (DOFDPs): theory and clinical consequences / Robert C. Supple, DMD -- Force finishing in dental medicine: a simplified approach to occlusal harmony / Sushil Koirala.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 02/04/2015).
Keywords: Malocclusion -- Diagnosis; Dentistry -- Information technology; Occlusion (Dentistry); Malocclusion -- diagnosis; Dental Occlusion; Dental Stress Analysis -- instrumentation; Image Processing, Computer-Assisted -- methods; Jaw Relation Record -- instrumentation; Malocclusion -- radiography; Abfraction formation and root recession defects; Adhesive and esthetic prostheses; Implant prosthodontics; Natural tooth occlusal function; Orthodontics; Prosthodontics; Temporomandibular disorders; Electronic books